Distribution, Function and Regulation of Type 6 Secretion Systems of Xanthomonadales - Bayer-Santos, Ethel; Ceseti, Lucas de Moraes; Farah, Chuck Shaker; Alvarez-Martinez, Cristina Elisa (Frontiers in Microbiology, 2019)
Members of the Xanthomonadales order include several plant pathogens of significant economic and agricultural impact, such as Xanthomonas spp. Type six secretion systems (T6SSs) are contractile nanomachines used by many bacterial species to inject protein effectors into target prokaryotic and eukaryotic cells and provide a competitive advantage for bacteria in different environments. Effectors with antibacterial properties include peptidoglycan hydrolases, lipases and phospholipases that break down structural components of the cell envelope, promoting target-cell lysis; and RNases, DNAses and NADases that affect target-cell metabolism, arresting growth. Effectors with anti-eukaryotic properties are functionally more diverse. The T6SS of Xanthomonas citri is the only example experimentally characterized so far within the Xanthomonadales order and displays anti-eukaryotic function by providing resistance to predation by amoeba. This T6SS is regulated at the transcriptional level by a signaling cascade involving a Ser/Thr kinase and an extracytoplasmic function ECF sigma factor. In this review, we performed in silico analyses of 35 genomes of Xanthomonadales and showed that T6SSs are widely distributed and phylogenetically classified into three major groups. In silico predictions identified a series of proteins with known toxic domains as putative T6SS effectors, suggesting that the T6SSs of Xanthomonadales display both anti-prokaryotic and anti-eukaryotic properties depending on the phylogenetic group and bacterial species.